Communication as the Axis of a Change in Administrative Style in a Higher Education Institution - Ortega Carrillo, Miguel Agustín; Caldera Gonzalez, Diana del Consuelo; Arredondo Hidalgo, María Guadalupe (Technium Social Sciences Journal, 2025)
This work arises from a project developed in a higher education institution, aimed at identifying areas for improvement in internal communication and strengthening training courses for operational staff. From a theoretical analysis, the need has been observed to move from a predominantly coercive administrative model toward one oriented toward participatory leadership. Therefore, this study presents an analysis of paradigms in administrative styles, starting from the traditional conception and highlighting the advantages of a contemporary approach that pays greater attention to the human dimension, thus fostering a more effective dynamic with the members of the organization. The work is structured into three clearly differentiated parts. The first offers a brief explanation of the difference between the administrative style proposed for implementation and the traditional style, based on the principles of classical and scientific management. The second part delves into how communication constitutes the backbone of the proposed contemporary style, where attention and trust-building among members become more relevant than the exercise of authoritarian control. Finally, the third part describes how some of the aspects reviewed in theory have begun to be operationalized for practical application, which will lead to a subsequent work presenting the results of the organizational intervention in the higher education institution, based on these premises. For the practical application of this conceptual model, a series of inter-institutional efforts are being developed within the educational organization to implement a different administrative style. In practice, obstacles and details evidencing some resistance to change have continued to arise, making the comprehensive adoption of these notions difficult. Nevertheless, thanks to the management’s willingness to promote positive transformations, it is expected that a successful intervention—albeit with some nuances—will be carried out, allowing for an evaluation of the results in terms of communication and administration, derived from the implementation of the practices proposed in this conceptual model.